Transfusion of fresher versus older red blood cells for all conditions - Brunskill, S; Wilkinson, K; Trivella, M; al., E (John Wiley and Sons, 2015)
Background Red blood cell transfusion is a common treatment for anaemia in many clinical conditions. One current concern is uncertainty as to the clinical consequences (notably efficacy and safety) of transfusing red blood cell units that have been stored for different durations of time before a transfusion. If evidence from randomised controlled trials were to indicate that clinical outcomes are affected by storage age, the implications for inventory management and clinical practice would be significant. Objectives To assess the effects of using fresher versus older red blood cells in people requiring a red blood cell transfusion. Search methods We ran the search on 29th September 2014. We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (OvidSP), Embase (OvidSP), CINAHL (EBSCO), PubMed (for e-publications), three other databases and trial registers. Selection criteria We included randomised controlled trials comparing fresher red blood cell transfusion versus active transfusion of older red blood cells, and comparing fresher red blood cell transfusion versus current standard practice. All definitions of ’fresher’ and ’older’/’standard practice’ red blood cells were included. Data collection and analysis Two review authors independently assessed trial quality and extracted from the trial report data on adverse red blood cell transfusion reactions, when reported.